Children’s Doctors Against the War: Call for Action Now - Valiulis, Arūnas (Acta medica Lituanica, 2022)
Two weeks have passed since the beginning of the invasion of Ukraine. Despite 141 countries voting in the UN General Assembly for the Russian army to stop fighting and withdraw from another sovereign country, Ukraine, the fighting is increasingly bloody and brutal. The war has led to 2.5 million people including about 1 million children fleeing from their homes and becoming refugees. There are 79 children confirmed killed including 18 months old infant in Mariupol. Most of child fatalities result from attacks from the air or with rockets. We stand together with Ukrainian children, families and the heroic medical and nursing staff calling for the action now: • we ask the governments of our countries to do more to ensure the safety of children in Ukraine, to stop the war and first of all to stop rockets and bombs attacks on civil infrastructure of Ukraine; • we ask Russian paediatricians and especially leaders of paediatric organizations in Russia to express clear and loud position against the war in Ukraine and to do everything in their power to stop the war; • we confirm once again solidarity and professionalsupport for children’s doctors and nurses in Ukraine. Our voices are stronger than rockets and bombs! Slava Ukraine!